Management education at the crossroads - Rivera, Claudio Andrés (knjige, 2021)
The poster session has become a valuable addition to the CEEMAN Annual Conference. It offers a platform for faculty and researchers to share their latest work in teaching and research, best practices, and ideas, in a fast-paced and engaging format.
Keywords: Izobraževanje; Management; Mednarodna posvetovanja; zborniki